Jesus the priest - Perrin, Nicholas (Grand Rapids, MI : Baker Academic, 2018)
Following his critically acclaimed book Jesus the Temple, Nicholas Perrin offers a fresh paradigm for understanding the historical Jesus. Perrin challenges the "standard reading" of classic texts (including the parable of the sower, the Beatitudes, and the Lord's Prayer) to argue that the historical Jesus primarily identified himself not as sage or prophet but as Israel's eschatological high priest. Perrin's insightful theological contribution synthesizes the best in traditional/conservative and liberal reconstructions of Jesus's life and teaching. He identifies Jesus's priesthood as a mediating understanding that sheds crucial light on the kingdom of God.
The prayer of Jesus -- The baptism of Jesus -- The kingdom of Jesus -- Jesus son of David -- The identity of the Son of Man -- A re-envisaged priesthood -- Final confrontations.
Includes bibliographical references (pages 291-323) and indexes.
Keywords: Jesus Christ -- Priesthood -- Biblical teaching; Jesus Christ -- Person and offices; Jesus Christ -- Biography -- Public life